Coating deposition using vacuum arc and ablation metal plasma - Ryabchikov A. I. Aleksandr Ilyich
An innovative concept in the development of advanced coating deposition and ion implantation method including an application of filtered DC metal plasma or ablation plasma and high-frequency short-pulsed negative bias voltage with a duty factor in the range 10-99% is considered. The regularities of metal ion implantation and vacuum arc metal plasma or ablation plasma deposition for conducting and insulating materials are considered. It was shown that plasma based ion implantation as well as high-concentration plasma ion implantation with compensation of ion surface sputtering by plasma deposition as well as ionassistedcoating deposition may be realized for metal and dielectric samples by variation of negative biaspotential in the range of 0-4·103 V, pulse repetition rate smoothly adjusted in the range of (2-4.4)×105 pps and pulse duration in the range of 0.5-2 μs. It was experimentally shown that at coating deposition from ablation plasma obtained by high intensity ion beam (j=300 A/cm2, E=350 keV, τ=90 ns) influence on the target, the breakdown of the plasma sheet occurred at dc negative bias potential on a substrate more than 60 V. The transfer to 0.5 μs duration pulses allowed us to increase the bias potential up to −4 kV. The possibility of high-frequency, short-pulsed plasma-immersion ion implantation and deposition method application for coating deposition from vacuum arc and ablation plasma with high adhesive strength andimproved exploitation characteristics is discussed in the paper